“The impact of the critical factors for the transfer of knowledge on opportunities and strategic success” - الكبيسي, صلاح الدين عواد; حسن, رنا فلاح (Journal of Economics and Administrative Sciences, 2017)
The current research discusses “The impact of the critical factors for the transfer of knowledge on opportunities and strategic success ", the attention have been increased on knowledge transfer and strategic success subjects because on being one of the important and contemporary issues, which have a significant impact on the existence of organizations and its future. The research aims to identify the critical factors for knowledge transfer in private high education environment which enables (the college community surveyed) to achieve strategic success, also the research sought to answer questions related to research problem by testing a number of major and minor hypothes in impact, in order to test the hypotheses I used a field study and applied it on a sample of deans, head departments and their assistant in a number of colleges in Baghdad City and was (60) person, data was collected by questionnaire as a key tool to search, she also used a number of statistical methods for data processing, including: The arithmetic mean, standard deviation, and simple regression coefficient and multiple, the most significant outcome of the research was a impact existence of critical factors for knowledge transfer (knowledge properties, the source of knowledge, recipients of the knowledge, organizational context) in strategic success opportunities, finally found the good use of the research samples impact. the study concluded a set of recommendations which was the need to invest the critical factors for knowledge transfer also sustain and develop these factors to maximize the added value that is reflected on strategic success, and support that through their ability to survive and adapt in a highly competitive environment and the need to employ it by private college administrations for critical factors of knowledge transfer dimensions which are (knowledge properties, the source of knowledge, recipients of the knowledge, organizational context), in a thorough contemporary overview than activated individually to enhance strategic success opportunities.